Assemblr Edu's AR Video Innovation for Hydrosphere Dynamics Learning at SMA Negeri 1 Sigi - Moh Saputra; Risma Fadilah Arsy; Suwarni; Zulnuraini (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to develop an Augmented Reality (AR) video-based learning resource using the Assemblr Edu application on the subject of hydrosphere dynamics for Year 10 students at State Senior High School 1, Sigi Regency, and to determine its suitability and practicality. This study employed the Research and Development (R&D) method using the ADDIE model, which comprises the analysis, design, development, implementation, and evaluation stages. Data collection techniques were carried out through expert validation questionnaires, teacher practitioner assessments, student response questionnaires, and interviews. The results of the study indicate that the developed learning media is classified as highly feasible, with a content validation rate of 90%, a media validation rate of 100%, and a teacher practitioner assessment rate of 88%. Furthermore, the pilot test results showed a practicality level of 83% and a student response rate of 91%, both falling within the ‘highly practical’ category. These results indicate that the Augmented Reality-based learning media using Assemblr Edu is capable of enhancing learning motivation, facilitating the understanding of abstract concepts, and creating a more interactive learning experience. Consequently, the developed learning media is suitable for use as an innovation in geography education.